The violence of language : contemporary hate speech and the suitability of legal measures regulating hate speech in South Africa - Janse van Rensburg, Leanne (Rhodes University, Faculty of Law, Law, 2013)
This thesis unites law and social science so as to give a comprehensive account of the phenomenon of racial hate speech in South Africa as an obstacle to transformation. Hate speech is presented as a form of violent language and an affront to the constitutional rights of freedom of speech, equality and dignity. To establish the nature of hate speech, the fluid quality of language is explored so as to show how language can be manipulated, on the one hand, as a means to harm, and employed, on the other hand, as a tool to heal and reconcile. This double gesture is illustrated through the South African linguistic experience of past hate and segregation and the current transformation agenda. It is through this prism that hate speech regulation is discussed as an uneasy fit in a country where freedom of expression is constitutionally protected and where language plays an important role in bringing about reconciliation, and yet words are still being employed to divide and dehumanise. This reality necessitates a clearly articulated stance on the regulation of language. The thesis accordingly interrogates the current legal standards in relation to hate speech with reference to international law that binds South Africa and the constitutional standard set for the regulation of language and the prohibition of hate speech. Thereafter, the current and proposed legislative prohibitions on hate speech, the residual common law provisions governing expression and the regulation of language in the media are outlined and analysed. These legal frameworks are explored in terms of their content and their application in various fora so as to ascertain what the South African approach to hate speech prohibition is, whether it is consistent and, ultimately if it is indeed suitable to the South African experience and the realities of language. This thesis concludes that contemporary hate speech measures lack a coherent understanding of what hate speech entails and a general inconsistency in approach as well as application is found in the treatment of hate speech complaints in South Africa. This is explained through the fallibility of language as a medium to regulate expression and solutions are offered to not only taper current and proposed hate speech provisions but to also consider alternative forms of resolving hate speech complaints
Keywords: Hate speech -- South Africa; Hate speech -- Law and legislation -- South Africa; Racism in language; Freedom of speech -- South Africa